2022 Microwave Mediterranean Symposium (MMS) 2022
DOI: 10.1109/mms55062.2022.9825558
|View full text |Cite
|
Sign up to set email alerts
|

GaN-based Single Stage Low Noise Amplifier for X-band Applications

Abstract: Source degenerated HEMTs are used to achieve good noise matching and better input return loss without degrading the noise figure and reducing the stability. This work presents an MMIC design for the frequency band of 8 -11 GHz by using HEMTs with source degeneration in 0.15 μm GaN on SiC technology. All design work is done in the Advanced Design System. The LNA delivers more than 6.9 dB gain with better than 8.5 dB and 9.5 dB input and output return losses, respectively. In addition, the gain ripple is around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…On the other hand, 2‐stage LNA (LNA‐2) has an NF of 1.7 dB, a flat gain response of 16.8 dB, and input and output return losses of 8.8 and 10 dB, respectively. Furthermore, Caglar et al 12 have demonstrated a single‐stage LNA MMIC design that employs HEMTs with source degeneration in 0.15 μm GaN on SiC technology. This arrangement offers an enhanced noise figure (1.1 dB), gain (>6.9 dB), and fairly good input and output return losses (8.5 and 9.5 dB, respectively) for the frequency range of 8–11 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 2‐stage LNA (LNA‐2) has an NF of 1.7 dB, a flat gain response of 16.8 dB, and input and output return losses of 8.8 and 10 dB, respectively. Furthermore, Caglar et al 12 have demonstrated a single‐stage LNA MMIC design that employs HEMTs with source degeneration in 0.15 μm GaN on SiC technology. This arrangement offers an enhanced noise figure (1.1 dB), gain (>6.9 dB), and fairly good input and output return losses (8.5 and 9.5 dB, respectively) for the frequency range of 8–11 GHz.…”
Section: Introductionmentioning
confidence: 99%